2005
DOI: 10.1111/j.1461-0248.2005.00823.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of macroalgal species identity and richness on primary production in benthic marine communities

Abstract: Plant biodiversity can enhance primary production in terrestrial ecosystems, but biodiversity effects are largely unstudied in the ocean. We conducted a series of field and mesocosm experiments to measure the relative effects of macroalgal identity and richness on primary productivity (net photosynthetic rate) and biomass accumulation in hard substratum subtidal communities in North Carolina, USA. Algal identity consistently and strongly affected production; species richness effects, although often significent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
177
3
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(205 citation statements)
references
References 47 publications
(88 reference statements)
17
177
3
2
Order By: Relevance
“…For example, Bruno et al (7) found that algal species richness had little, if any, effect on biomass production in 2.5-to 5-week mesocosm experiments, whereas 2 longer-term field manipulations (Ͼ1 year) found strong effects (14,15). However Bruno et al (7,8) also performed field experiments with the same species pool and still found weak or no effect of species richness, so the distinction is not simply due to the field setting. Two major differences between the field experiments that found effects of species richness and those that did not are (i) the duration of the experiment and (ii) whether treatments were produced by assembling transplanted individuals vs. deleting species in situ on natural substrates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Bruno et al (7) found that algal species richness had little, if any, effect on biomass production in 2.5-to 5-week mesocosm experiments, whereas 2 longer-term field manipulations (Ͼ1 year) found strong effects (14,15). However Bruno et al (7,8) also performed field experiments with the same species pool and still found weak or no effect of species richness, so the distinction is not simply due to the field setting. Two major differences between the field experiments that found effects of species richness and those that did not are (i) the duration of the experiment and (ii) whether treatments were produced by assembling transplanted individuals vs. deleting species in situ on natural substrates.…”
Section: Discussionmentioning
confidence: 99%
“…Although longer-term studies do tend to find strong effects, these studies are also from colder temperate regions, are conducted intertidally, and are in the field (14)(15)(16). In contrast, studies that find weak or no effects often involve subtidal taxa and are shorter term and/or conducted in mesocosms (7,8,17). This severely limits our ability to use existing data to ascertain when diversity really is and is not an important driver of ecosystem processes.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…This synthetic review has highlighted the importance of the identity of species or ''functional'' group in determining key processes in both soft and hard intertidal and shallow water communities. As such it reflects the rich history of empirical studies on both sides of the Atlantic, but also adds weight to recent output from the biodiversity-ecosystem-functioning debate that understanding of what species or taxa ''do'' is fundamental to understanding community and ecosystem ecology (e.g., Bruno et al 2005, Hooper et al 2005. Interestingly on rocky shores the identity of dominant grazers clearly has a strong role in determining the processes by which communities are structured.…”
Section: Conclusion and Future Researchmentioning
confidence: 99%
“…Nevertheless, the dual interpretation of the sampling effect illustrates the importance of food identity. Bruno et al (2005) noted that species identity generally appears to be much more important than species richness in controlling primary biomass production in a benthic marine community. Here some evidence of an effect of primary producers' identity on food selection by marine grazers is provided, hence influencing energy transfer to higher trophic levels.…”
Section: Discussionmentioning
confidence: 99%